A composite neural electrode and a preparation method and application thereof

CN122912152APending Publication Date: 2026-10-16SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611427624.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

现有的静电纺丝薄膜虽具有多孔结构,但导电层分布于纤维壳层或通过溅射/沉积于表面,电极位点不可定点控制,溅射后导电材料容易扩散到多孔网络中引起信号的串扰,且平面薄膜形态植入创伤大

Benefits of technology

[0055]本发明提供的复合神经电极从微观到宏观均为纤维形态,植入创伤小,兼具高密度电极触点、可降解和药物控释功能,在脑机接口领域具有广阔的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912152A_ABST
    Figure CN122912152A_ABST
Patent Text Reader

Abstract

The application provides a composite nerve electrode and a preparation method and application thereof. The composite nerve electrode comprises a porous fiber membrane and a plurality of composite fibers, the plurality of composite fibers are fixed on the surface of the porous fiber membrane and are curled to form the composite nerve electrode; the composite fiber comprises a conductive fiber and an insulating encapsulation layer, and an area where a first end of the conductive fiber is not covered by the insulating encapsulation layer constitutes an electrode point; the porous fiber membrane is loaded with a drug and has a multi-level pore structure, which comprises inter-fiber micrometer-level pores and nanometer-level fiber surface pores; a first end of the composite nerve electrode is a contact area composed of a plurality of electrode points, a second end of the composite fiber is led out from a main body structure of the composite nerve electrode, and an intermediate area is wrapped by the curled porous fiber membrane. The composite nerve electrode has porosity, high channel density and fixed electrode points, and is suitable for application in the field of brain-computer interfaces.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the fields of biomedical materials and neural engineering technology, specifically relating to a composite neural electrode, its preparation method, and its application. Background Technology

[0002] The rapid development of neurointerventional technologies such as brain-computer interfaces, deep brain stimulation, and stereotactic electroencephalography (EEG) has placed extremely high demands on the performance of neural electrodes. An ideal neural electrode needs to integrate high-density channels in the smallest possible space to achieve high-resolution signal acquisition, while the electrode's mechanical properties, biodegradability, and drug release function must be highly compatible with the in vivo microenvironment.

[0003] Traditional silicon-based or tungsten-based electrodes have an elastic modulus in the GPa range, which is several orders of magnitude lower than that of brain tissue in the kPa range. This makes them prone to immune rejection and glial scarring after implantation. While flexible substrates such as polyimide offer some improvement, their modulus is still in the GPa range. Furthermore, the dense structure of polyimide substrates can affect the nutrient and metabolic circulation around the device after implantation.

[0004] Fiber-based electrodes have attracted attention due to their minimal implantation trauma and flexibility. For example, existing technology CN202211230147.0 uses PEDOT:PSS as raw material to obtain fiber electrodes with a modulus in the range of 50-1000 kPa through wet spinning, achieving mechanical matching with brain tissue. However, the surface area of ​​a single fiber is extremely limited, the number of integrateable electrode sites is usually small, and the spatial resolution is severely limited. Another study ("Elastocapillary self-assembled neurotassels for stable neural activity recordings") fabricated fibrous electrodes, which were encapsulated with polyimide and hardened with polyethylene glycol to obtain a fibrous tassel electrode structure. However, the randomness of the tassels after unraveling can lead to movement in the body, affecting signal stability and neuronal localization and real-time monitoring. Furthermore, the polymer material used is non-degradable, requiring a secondary surgery for removal.

[0005] To simultaneously reduce implantation trauma and increase channel density, researchers have rolled planar films into fibrous structures to form rolled electrodes. For example, high-density conductive patterns are formed on the surface of a polyimide film through photolithography and sputtering, and then rolled into shape, allowing the integration of hundreds of electrode sites within a micrometer diameter. However, existing rolled electrodes typically use dense, non-porous substrate films, which hinder material exchange after implantation and can easily lead to chronic inflammation in the long term; moreover, these rolled electrodes are usually non-biodegradable and require surgical removal.

[0006] The porosity of electrospun fiber network films offers the potential to improve electrode-tissue interface compatibility. However, fabricating high-density and cross-sectionally stable electrodes on the surface of electrospun films presents challenges. For example, prior art CN202211624242.9 fabricates three-dimensional wrinkled neural electrodes through electrospinning combined with spraying / vapor deposition. However, in the formed neural electrodes, the conductive components are distributed in the fiber shell, and the electrode sites cannot be precisely controlled; moreover, due to the porous structure of the electrospun film, conductive materials easily expand into the fiber network during sputtering, leading to signal crosstalk during testing. Another prior art CN202080028429.5 uses nylon electrospun fibers as a substrate, forming electrode patterns on its surface through photolithography, with moduli ranging from 50 MPa to 5 GPa. Because its conductive layer is formed on the fiber surface by sputtering or deposition, the interfacial adhesion is weak, making it prone to peeling over time, and planar implantation can lead to significant trauma.

[0007] Therefore, while existing coiled electrodes can achieve high channel density, the films used are dense, non-porous, and non-degradable. Existing electrospun films, although possessing porous structures, have conductive layers distributed within the fiber shell or deposited on the surface via sputtering / deposition. Electrode sites cannot be precisely controlled, and after sputtering, conductive materials easily diffuse into the porous network, causing signal crosstalk. Furthermore, planar film implantation is highly invasive. Therefore, the challenge lies in designing a neural electrode that maintains porosity and degradability while achieving high channel density and precise electrode sites, thus resolving the difficulty of balancing high channel density and tissue compatibility in existing neural electrodes. Summary of the Invention

[0008] To solve all or part of the above-mentioned technical problems, the present invention provides the following technical solutions: A first aspect of the present invention provides a composite neural electrode comprising a porous fiber membrane and multiple composite fibers, wherein the composite neural electrode has a helical structure formed by fixing multiple composite fibers to the surface of the porous fiber membrane and curling them up. The composite fiber includes conductive fibers and an insulating encapsulation layer. The insulating encapsulation layer is formed on a portion of the outer surface of the conductive fiber. The area at the first end of the conductive fiber not covered by the insulating encapsulation layer constitutes an electrode point. The porous fiber film has a multi-level pore structure, which includes micron-level inter-fiber pores and nano-level fiber surface pores. The porous fiber film is loaded with a drug. The first end of the composite nerve electrode is a contact area, which is composed of multiple electrode points; the second end of the composite fiber extends from the main structure of the composite nerve electrode and is used to connect to an external circuit; the middle region of the composite fiber is wrapped with a curled porous fiber membrane.

[0009] The composite neural electrode provided by this invention uses a porous fiber membrane with a multi-level pore structure as a substrate. The micron-level pores provide channels for material exchange and drug release, while the nano-level pores increase the specific surface area and provide drug loading sites. Drugs loaded in the membrane can be precisely released at the tissue interface where the electrode contacts are located. Electrode points on conductive fibers are integrated at the first end (i.e., the contact area) of the composite neural electrode. The number of electrode contacts equals the number of conductive fibers, thus achieving a balance between high channel density and minimally invasive implantation.

[0010] In some embodiments, the porous fiber film is an electrospun film.

[0011] In some embodiments, the porous fiber membrane includes a first biodegradable material and a drug.

[0012] In some embodiments, the mass ratio of the first biodegradable material to the drug in the porous fiber membrane is 2.4:1 to 20000:1.

[0013] In some embodiments, the first biodegradable material includes one or more combinations of polylactic acid-glycolic acid copolymer, L-polylactic acid, polycaprolactone, polylactic acid, or silk fibroin, but is not limited thereto.

[0014] In some embodiments, the drug includes one or a combination of anti-inflammatory drugs, neurotrophic factors, neurotransmitters, and antibacterial drugs. The anti-inflammatory drugs include, for example, one or a combination of dexamethasone, minocycline, and curcumin; the neurotrophic factors include, for example, one or a combination of nerve growth factor and brain-derived neurotrophic factor; the neurotransmitters include, for example, one or a combination of dopamine and glutamate; and the antibacterial drugs include, for example, one or a combination of tetracycline and vancomycin. However, the selected drug is not limited to the specific drugs mentioned above, and the drug type can be replaced according to actual needs.

[0015] In some embodiments, the porous fiber film contains fibers with a certain orientation, and the orientation factor is 0.1-0.9.

[0016] In some embodiments, the conductive fiber comprises a second biodegradable material and a conductive material in a mass ratio of 0.6:1 to 50:1.

[0017] In some embodiments, the conductivity of the conductive fiber is 0.01 ~ 200 S / cm.

[0018] In some embodiments, the diameter of the conductive fiber is 10 μm to 200 μm.

[0019] In some embodiments, the second biodegradable material includes silk fibroin nanofibers and / or regenerated silk fibroin. Silk fibroin nanofibers are preferred because they exhibit high stability when mixed with materials such as nanotubes, without significant precipitation or aggregation. The mixed solution is also more stable during storage, which is beneficial for preparing fibers with uniform structures.

[0020] In some embodiments, the conductive material includes, but is not limited to, one or more of MXene, carbon nanotubes, graphene, PEDOT:PSS, metal nanowires, or salt ions. The metal nanowires include, for example, silver nanowires, and the salt ions include, for example, one or more of sodium ions, calcium ions, potassium ions, or lithium ions.

[0021] In some embodiments, the insulating encapsulation layer is preferably also made of a biodegradable material, such as a combination of one or more of polylactic acid-glycolic acid copolymer, polycaprolactone, and polylactic acid.

[0022] In some embodiments, the outer surface of the composite neural electrode further includes a temporary hardening layer. This temporary hardening layer can swell after the composite neural electrode is implanted into a living organism.

[0023] In some embodiments, the temporary hardening layer is made of regenerated silk fibroin. The temporary hardening layer formed by regenerated silk fibroin can increase the dry elastic modulus of the composite neuroelectrode (e.g., 1 MPa to 100 MPa), facilitating implantation. After implantation, the surface silk fibroin gradually swells, and the wet elastic modulus decreases (e.g., to 100 kPa to 10 MPa) to match the biomechanics of brain tissue.

[0024] In some embodiments, when the composite fiber is fixed to the surface of the porous fiber membrane, the composite fiber and at least one edge of the porous fiber membrane are inclined at an angle of 10° to 80°.

[0025] In some embodiments, multiple composite fibers are fixed to the surface of the porous fiber membrane in a parallel arrangement. For example, the distance between adjacent composite fibers is 20 μm to 1000 μm.

[0026] In some embodiments, the dry elastic modulus of the composite neural electrode is 1 MPa to 100 MPa, and the wet elastic modulus is 100 kPa to 10 MPa.

[0027] A second aspect of the present invention provides a method for preparing a composite neural electrode, comprising: A first spinning solution comprising a first biodegradable material and a drug is provided, and the first spinning solution is used to form a porous fiber membrane loaded with the drug using an electrospinning process. A second spinning solution containing a second biodegradable material and a conductive material is provided. The second spinning solution is used to form conductive fibers, and an insulating encapsulation layer is covered on a portion of the surface area of ​​the conductive fibers. The insulating encapsulation layer does not cover the first end of the conductive fibers to form exposed electrode points, thereby obtaining composite fibers. Multiple composite fibers are fixed to the surface of the porous fiber membrane, then rolled up, and after shaping, a spiral composite nerve electrode is obtained. The first end of the composite nerve electrode is a contact area, which is composed of electrode points on multiple composite fibers; the second end of the composite fiber extends from the main structure of the composite nerve electrode and is used to connect to an external circuit; the middle region of the composite fiber is wrapped by a curled porous fiber membrane.

[0028] In some embodiments, the content of the first biodegradable material in the first spinning solution is 5-20 wt%.

[0029] In some embodiments, the drug content in the first spinning solution is 0.01 mg / mL to 31 mg / mL.

[0030] In some embodiments, the conditions for the electrospinning process include: a voltage of 10-25 kV, a receiving distance of 10-20 cm, a feed speed of 0.5-3 mL / h, and a receiving speed of 50-2000 rpm. During the spinning process, the orientation factor can be adjusted by changing the roller receiving speed.

[0031] In some embodiments, the content of the second biodegradable material in the second spinning solution is 3-24 wt%.

[0032] In some embodiments, the content of conductive material in the second spinning solution is 2 mg / mL to 50 mg / mL.

[0033] In some embodiments, the method of forming conductive fibers from the second spinning solution includes any one of wet spinning, dry spinning, and 3D printing.

[0034] Wet spinning involves extruding the fiber into a coagulation bath using wet spinning equipment. After coagulation and shaping, the fiber is drawn and dried to obtain conductive fibers. The coagulation bath can be one or a combination of saturated ammonium sulfate solution, saturated sodium chloride solution, saturated calcium chloride solution, ethanol solution, methanol solution, polyethylene glycol solution, and polyvinyl alcohol solution. The draw ratio of wet spinning can be 1-3 times, and the drying temperature can be room temperature to 80℃.

[0035] 3D printing is a process in which conductive fibers are formed by extruding spinning liquid through the needle of a 3D printer and then solidifying it.

[0036] The raw materials for preparing conductive fibers by wet spinning and 3D printing include a liquid crystal suspension of silk fibroin nanofibers and conductive materials. The silk fibroin nanofibers in the suspension have a complete crystalline structure and exhibit liquid crystal orientation characteristics in a shear flow field, which promotes the orientation and alignment of conductive materials and improves conductivity.

[0037] Dry spinning refers to the process of extruding spinning solution through a needle, followed by solvent evaporation in the air to obtain conductive fibers. For example, the raw materials for preparing conductive fibers using dry spinning may include silk fibroin nanofibers, formic acid, calcium chloride, and a chemical crosslinking agent. The chemical crosslinking agent may include one or more combinations of polyethylene glycol diglycidyl ether, genipin, and 1,4-butanediol diglycidyl ether.

[0038] In some embodiments, the method of covering a portion of the surface area of ​​a conductive fiber with an insulating encapsulation layer includes: applying a solution containing an insulating encapsulation material to the surface of the conductive fiber to form an insulating encapsulation layer, and then removing the insulating encapsulation layer in a portion of the area by solvent etching to form exposed electrode points.

[0039] In some embodiments, the insulating encapsulation material includes one or a combination of polylactic acid-glycolic acid copolymer, polycaprolactone, and polylactic acid.

[0040] In some embodiments, the concentration of the solution containing insulating encapsulation material is 2wt% to 10wt%.

[0041] In some embodiments, the solvent etching uses acetone or a mixture of dichloromethane and dimethylformamide as the etching agent.

[0042] In some embodiments, the preparation method further includes: after the shaping, subjecting the obtained composite neural electrode to a temporary hardening treatment, the temporary hardening treatment including: immersing it in a regenerated silk fibroin solution, removing it and drying it, and then performing physical or chemical treatment to form a temporary hardened layer on the outer surface of the composite neural electrode.

[0043] In some embodiments, the concentration of the regenerated silk fibroin solution is 1-5 wt%.

[0044] In some embodiments, the physical treatment includes either steam treatment or heating. For example, placing it in steam and maintaining it for 60-180 minutes.

[0045] In some embodiments, the chemical treatment includes: impregnation with an aqueous solution containing methanol and / or ethanol. The aqueous solution containing methanol and / or ethanol has a methanol and / or ethanol content of 60-90%, and the impregnation time is 10-20 minutes.

[0046] The aforementioned physical and / or chemical treatments can regulate the secondary structure of silk fibroin, maintaining its good mechanical properties and stability in a wet state. The surface silk fibroin temporarily hardens the composite neural electrode, facilitating implantation; and after implantation, the silk fibroin gradually absorbs water and swells, reducing its modulus and forming flexible contact with surrounding tissues, thus improving the interfacial compatibility between the electrode and surrounding tissues.

[0047] In some embodiments, multiple composite fibers are fixed to the surface of a porous fiber membrane in a parallel arrangement, for example, the distance between adjacent composite fibers is 20 μm to 1000 μm.

[0048] In some embodiments, when the composite fiber is fixed to the surface of the porous fiber membrane, the composite fiber is inclined at an angle of 10 to 80° to at least one edge of the porous fiber membrane.

[0049] In some embodiments, multiple composite fibers are fixed to the surface of a porous fiber membrane by hot pressing. For example, the hot pressing temperature is 60~100℃, the pressure is 0.2~2MPa, and the hot pressing time is 1-12h.

[0050] In some embodiments, the shaping method is heat shaping. For example, it is maintained at a temperature of 60~120°C for 30~300 minutes.

[0051] For example, the preparation method of the composite neural electrode specifically includes the following steps: (1) Silk fibroin nanofibers are mixed evenly with conductive materials to prepare a spinning solution, and conductive fibers are obtained by extrusion molding strategy; (2) Coating or depositing a biocompatible insulating material on the surface of the conductive fiber to form an insulating encapsulation layer, removing part of the insulating encapsulation layer by solvent etching to form exposed electrode sites, and obtaining composite fiber; (3) A porous fiber membrane is made by electrospinning a solution containing biodegradable polymers and therapeutic drugs; (4) Multiple composite fibers are fixed to the surface of a porous fiber film in a parallel arrangement and then fixed by hot pressing; (5) The composite fibers are coiled along the edge with the direction of the fiber arrangement as the central axis to form a spiral structure, and then fixed by heat setting to form a composite nerve electrode. The coiling method satisfies the following: the exposed electrode point on the composite fiber is located at the first end of the spiral structure to form the contact area, one end of the composite fiber is led out from the main part of the spiral structure, and the middle section of the composite fiber is wrapped and fixed by the coiled porous fiber membrane. (6) Immerse the composite nerve electrode obtained in step (5) in a regenerated silk fibroin solution, take it out and air dry it, and then treat it by physical or chemical means to obtain a composite nerve electrode with a temporary hardening layer.

[0052] The further specific selection of materials involved in the second aspect of this invention, such as the first biodegradable material, the second biodegradable material, the conductive material, and the insulating encapsulation material, has been specifically described in the first aspect of this invention and will not be repeated here. The composite neural electrode described in the first aspect of this invention can be prepared using the preparation method described in the second aspect of this invention.

[0053] A third aspect of the present invention provides a composite neural electrode, which is prepared by the preparation method described in any of the technical solutions.

[0054] A fourth aspect of the present invention provides a brain-computer interface device comprising the composite neural electrode described in any of the technical solutions.

[0055] The composite neural electrode provided by this invention is fibrous in both microscopic and macroscopic dimensions, resulting in minimal implantation trauma. It also features high-density electrode contacts, biodegradability, and controlled drug release, making it a promising candidate for brain-computer interfaces.

[0056] Compared with the prior art, the present invention has at least some or all of the following beneficial effects: (1) The composite neural electrode provided by the present invention uses a porous fiber membrane as a substrate. Compared with a dense membrane, the multi-level pore structure of the porous fiber membrane can achieve good drug loading and controllable release, promoting good material exchange after the electrode is implanted into the organism. Moreover, its modulus is lower than that of a dense membrane, which can be more mechanically similar to low-modulus brain tissue, reducing damage to the tissue. The electrode points on multiple composite fibers are integrated at one end of the composite neural electrode to form a high-density contact array. Thus, the composite neural electrode can achieve high channel density and fixed electrode sites while maintaining porosity, solving the problem that existing neural electrodes are difficult to balance high channel density and tissue compatibility.

[0057] (2) The composite neural electrode of the present invention may further have a temporary hardening layer, so that it maintains a high dry elastic modulus before implantation, which facilitates implantation puncture. After implantation, the temporary hardening layer gradually swells and the wet elastic modulus decreases to match the mechanical properties of brain tissue.

[0058] (3) The composite nerve electrode of the present invention uses biodegradable materials, which can avoid or reduce the need for secondary surgery to remove it after implantation. If the main body is biodegradable after removal, it can also reduce the burden of electronic waste on the environment after the implanted device is discarded. Attached Figure Description

[0059] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0060] Figure 1 This is a schematic diagram of the spiral-structured composite neural electrode prepared in Example 1; Figure 2 This is a schematic diagram of the cross-section of the spiral-structured composite neural electrode prepared in Example 1; Figure 3 This is a schematic diagram of curling an electrospun film with fixed composite fibers in Example 1; Figure 4 The stability graphs of the silk fibroin nanofiber / CNTs mixed solution prepared in step S1 of Example 1, and the silk fibroin / CNTs mixed solution as a control after preparation (corresponding to 0h), after 12h, and after 1 month. Figure 5 This is a SEM image of the conductive fiber prepared in Example 1; Figure 6 This is a polarized microscope image of the conductive fiber prepared in Example 1; Figure 7 This is a SEM image of the conductive fibers after knotting in Example 1; Figure 8 This is a SEM image of the electrospun film from Example 1; Figure 9 This is a microscope image of the composite fiber integrated with the electrospun film in Example 1; Figure 10 This is a morphological image of the composite neural electrode prepared in Example 1; Figure 11 The mechanical curves of the composite fiber prepared in Example 2 under wet and dry conditions are shown. Figure 12 These are SEM images of the electrospun films prepared using different biodegradable biomaterials in Examples 1-4; Figure 13 This is a topographic image of the composite neural electrode in Example 4; Figure 14 This is a photograph of the fiber orientation arrangement obtained by 3D printing using a 5.5 wt% silk fibroin nanofiber suspension in Example 7. Figure 15 This is an electron microscope image of the composite fiber obtained in Example 8 bonded to an electrospun film; Figure 16It is the electrospun fiber with an oriented structure obtained by high-speed rotation in Example 9; Figure 17 This is a diagram showing the diffusion changes of water droplets on the electrospun fibers with an oriented structure in Example 9; Figure 18 This is an optical microscope image of the cross-section of the composite neural electrode prepared in Example 10; Figure 19 These are SEM images of the electrospun films obtained under different electrospinning conditions in Example 11; Figure 20 This is an electron microscope image of the PLA thin film in Comparative Example 1; Figure 21 This is a comparison diagram of the water permeability of the electrospun film of Example 2 and the PLA film of Comparative Example 1. Detailed Implementation

[0061] The invention will be more fully understood through the following detailed description of its embodiments. The detailed embodiments disclosed herein are merely illustrative, and the invention may be embodied in various forms. Therefore, the specific functional details disclosed herein should not be construed as limiting, but rather as the basis for the claims.

[0062] In addition, unless otherwise specified, all raw materials used in the following embodiments can be purchased from the market or other sources, and all production and testing equipment used are known in the art, as are the testing methods used.

[0063] Unless otherwise specified, the percentage symbol "%" used in the specific embodiments of this invention refers to mass percentage.

[0064] The testing methods involved in the specific embodiments of the present invention are as follows: (1) Dry-state elastic modulus test method of composite nerve electrode: The mechanical properties of the composite electrode were tested using a mechanical tensile testing device. The test conditions included: clamping distance: 10 mm, tensile speed: 5 mm / min. The modulus was calculated by the slope of the linear region of the stress-strain curve.

[0065] (2) Test method for wet elastic modulus of composite nerve electrode: Before the test, the sample was soaked in phosphate buffer (10 mM) at 37°C for 20 min, and then the surface moisture was absorbed with filter paper to start the test. The test parameters were the same as those for dry modulus test.

[0066] (3) Methods for testing the drug release rate and in vitro drug release cycle of the composite neural electrode: To plot the standard curve: First, prepare a 2 mg / mL minocycline hydrochloride solution and dilute it with release solution (5 mL ethanol: 95 mL 10 mM PBS at pH 7.4) to obtain different concentration gradients. Measure the absorbance of different mixtures at 370 nm using a UV spectrophotometer and plot the concentration-absorbance standard curve.

[0067] Weigh a certain amount of the drug-loaded film, place it in the above buffer solution, take samples at regular intervals, measure the absorbance, and then calculate the drug concentration at this time by subtracting it from the standard curve.

[0068] (4) Cytotoxicity test methods: Preparation of extract: First, the membrane to be tested was cut into 1 cm × 1 cm pieces and sterilized by irradiation. Serum-containing complete culture medium was added at a ratio of 6 cm² / mL and incubated at 37°C for 24 h to prepare the extract. The extract was then filtered through a 0.22 μm filter membrane for sterilization before use.

[0069] L929 mouse fibroblast culture and sample loading: Cell seeding density was 100 μL per well (containing 1×10⁶ cells per well) in 96 wells. 4 Cells were cultured for 24 hours until fully adhered, after which the culture medium was aspirated. 100 μL of the above-mentioned membrane extract was added to the experimental group, while 100 μL of fresh culture medium was added to the blank control group. Cultures were continued for different number of days. Then, 10 μL of MTT solution was added, and the cells were incubated for 2.5 hours. 150 μL of DMSO was added and the mixture was shaken for 10 minutes to fully dissolve the crystals. The absorbance (OD) of each well was measured at 490 nm using a microplate reader.

[0070] Calculate cell viability: Cell viability (%) = [(OD value of experimental group - OD value of blank group) / (OD value of control group - OD value of blank group)] × 100%.

[0071] (5) In vitro degradation test method: First, weigh a 5 mL centrifuge tube and record the weight as W1. Accurately weigh 100 mg of fiber and place it in the centrifuge tube. Add 2 mL of PBS (10 mM phosphate buffer, pH=7.4), seal and transfer to a 37℃ oven. At the set time, use a syringe to aspirate the supernatant to avoid loss of small fragments after degradation. Dry at 60℃ to constant weight, and weigh the degraded sample and centrifuge tube together as W2. The formula for calculating the weight residue rate is as follows: Weight residue rate (%) = (W2-W1) / (100)×100%.

[0072] Example 1 This embodiment provides a composite neural electrode and its preparation method, specifically including the following steps: S1. 25g of silk (Hongtong Silk Technology Co., Ltd., raw silk, 5A) was cut into small pieces and then boiled in 5L of 0.05% (mass-to-volume) sodium carbonate solution for 30 minutes. After removing the silk, it was washed 5 times with deionized water and dried in an oven at 45℃ to constant weight to obtain degummed silk. A 2.5g / L potassium hydroxide solution was prepared, and the degummed silk was mixed with the alkaline solution at a bath ratio of 10g:1L. The mixture was magnetically stirred until the degummed silk was dispersed into silk fibroin nanofibers. The diameter of the obtained micro-nanofibers was approximately 60nm~700nm, the fiber length was approximately 1μm~50μm, and the yield was 62.7%. After centrifugation, dialysis, and ultrasonic dispersion, a 5wt% silk fibroin nanofiber suspension with good dispersibility was obtained. Carbon nanotubes (CNTs, as conductive materials) were dispersed in the above suspension at a concentration of 2 mg / mL. After ultrasonic dispersion, a silk fibroin nanofiber / CNTs mixed solution was obtained. This mixed solution was used as the spinning solution, wherein the mass ratio of silk fibroin to conductive material was 25:1.

[0073] The spinning solution was extruded into a coagulation bath using a 25G spinning needle. The coagulation bath was an ethanol / calcium chloride solution (with a calcium chloride content of 5 wt%). After being stretched twice, the solution was dried to obtain conductive fibers.

[0074] S2. The conductive fiber obtained in step S1 is coated with 5wt% polylactic acid to form an insulating encapsulation layer; then the insulating encapsulation layer at the first end of the conductive fiber is removed by etching with acetone to form exposed electrode points, thus obtaining a composite fiber.

[0075] S3. A biodegradable material (polylactic acid, PLA) and a drug (dexamethasone) were dissolved in dichloromethane to prepare an electrospinning solution, wherein the polylactic acid content was 10 wt% and the dexamethasone content was 0.5 mg / mL (the mass ratio of polylactic acid to drug was 200:1). Electrospinning was performed using this electrospinning solution under the following conditions: voltage of 15 kV, receiving distance of 15 cm, feed speed of 1 mL / h, and roller receiving speed of 200 rpm, to obtain an electrospinned film with a thickness of approximately 50 μm, which was then cut into an "L" shape.

[0076] S4. Take 8 composite fibers obtained in step S2, and arrange them in an "L" shape parallel to each other on the surface of the electrospun film obtained in step S3. One end of the composite fiber is inclined at a 20° angle to the edge of the electrospun film, and the spacing between adjacent composite fibers is 350 μm. Then, perform hot pressing fixation at 80℃ and 0.5MPa for 2 hours. Next, curl the composite fibers along the edge with the direction of their arrangement as the central axis, and heat set at 60℃ for 30 minutes to form a spiral composite neural electrode.

[0077] S5. Dissolve the degummed silk obtained in step S1 in a 9.3M lithium bromide aqueous solution (1g of degummed silk corresponds to 4mL of lithium bromide solution), place it in a 60℃ oven for 4 hours, remove it, dialyze it, and centrifuge it to obtain a regenerated silk fibroin solution. Immerse the composite neural electrode prepared in step S4 in a 3wt% silk fibroin solution, remove it, air dry it, and treat it with water vapor for 60 minutes to temporarily harden the composite neural electrode.

[0078] Figure 1 This is a schematic diagram of the spiral composite neural electrode obtained in Example 1. The first end of the composite neural electrode is a contact area, which includes multiple electrode points derived from the composite fiber that are not covered by an insulating encapsulation layer. The middle area of ​​the composite neural electrode is a support section, which includes a coiled electrospun film and a middle section of the composite fiber wrapped inside it. One end of the composite fiber is led out from the main structure of the composite neural electrode and is used to connect to an external circuit, which is the wiring and post-processing end of the composite neural electrode.

[0079] Figure 2 This is a schematic diagram of the cross-section of the helical composite neural electrode prepared in Example 1, as shown below. Figure 2 As shown, the composite fiber includes conductive fibers and an outer insulating encapsulation layer. The composite fibers are uniformly distributed in the spiral structure formed by the curling of the electrospun film. Drug molecules are uniformly doped in the electrospun film, and a regenerated silk fibroin temporary hardening layer is also formed on the outside of the composite nerve electrode.

[0080] Figure 3 This is a schematic diagram of the curling of an electrospun film with fixed composite fibers in Example 1, as shown below. Figure 3 As shown, the electrospun membrane is cut into an "L" shape, and the composite fibers are arranged in parallel "L" shapes and fixed on the porous fiber membrane. One end of the composite fiber forms a certain angle with one edge of the electrospun membrane. This can adjust the spatial distribution of each electrode point, so that after the entire electrode is implanted in the brain region, the neuronal signals distributed at different depths near the electrode can be tested.

[0081] Figure 4This is a stability graph showing the silk fibroin nanofiber / CNTs mixed solution prepared in step S1 of Example 1, and the silk fibroin / CNTs mixed solution used as a control after preparation (corresponding to 0h), after standing for 12h, and after standing for 1 month. The preparation method of the silk fibroin in the control silk fibroin / CNTs mixed solution includes: adding degummed silk to a 9.3M lithium bromide aqueous solution, where 1g of silk corresponds to 4mL of lithium bromide solution, dissolving at 60°C for 4h, then transferring to a dialysis bag (molecular weight cutoff of 3500 Da) and dialyzing in pure water for 3 days, changing the pure water every 6h during this period, finally obtaining a regenerated silk fibroin solution. Adding CNTs to this silk fibroin solution yields the silk fibroin / CNTs mixed solution. Figure 4 As shown, the silk fibroin nanofiber / CNTs mixed solution still exhibited uniform fluidity after being left to stand for different periods of time, and no obvious aggregation or precipitation was found after one month. Its stability was significantly higher than that of the carbon nanotube and silk fibroin solution.

[0082] Figure 5 This is a SEM image of the conductive fiber prepared in Example 1. The diameter of the conductive fiber prepared in this example is 114.6 ± 17.3 μm. Figure 5 Silk fibroin nanofibers and carbon nanotubes were observed to be uniformly dispersed. The dry elastic modulus was approximately 45.2 MPa, the wet elastic modulus was approximately 5.1 MPa, and the electrical conductivity was approximately 104.5 S / cm. Figure 6 This is a polarized light microscope image of the conductive fiber prepared in Example 1. Observation under a polarized light microscope shows that the conductive fiber exhibits significant birefringence. Figure 7 This is an SEM image of the conductive fiber from Example 1 after it was knotted. The knotted fiber did not break, demonstrating significant flexibility.

[0083] Furthermore, the diameter of the conductive fibers can be controlled by the concentration of the spinning solution and the type of spinning needle. Studies have shown that when the concentration of silk fibroin nanofibers in the spinning solution is 5 wt% and the needle type is 21G, the diameter of the resulting conductive fibers is approximately 160 μm. With a 25G needle, the diameter is approximately 110 μm, and with a 30G needle, the diameter is approximately 20 μm. When the concentration of silk fibroin nanofibers is 3 wt% and the needle type is 25G, the diameter is approximately 40 μm. It is foreseeable that the diameter of the conductive fibers is related to the process and the draw ratio, and can be controlled according to requirements.

[0084] Figure 8This is a SEM image of the electrospun film of Example 1, which has micron-sized inter-fiber pores formed by the random stacking of electrospun fibers, and nano-sized fiber surface pores formed by the phase separation of solvent evaporation during the spinning process. In the electrospun film of Example 1, the diameter of the inter-fiber pores is approximately 2-8 μm, and nano-sized pores with a diameter of approximately 50-200 nm and a porosity of 80% exist on the fiber surface.

[0085] Figure 9 This is a microscope image of the composite fiber and the electrospun film integrated in Example 1, illustrating that the composite fiber and the electrospun film can be stably combined. Figure 10 This is a morphological image of the composite nerve electrode prepared in Example 1. The composite fibers are uniformly arranged and have good bonding force with the electrospun film.

[0086] Example 2 Example 2 is basically the same as Example 1, except that: In step S1, the conductive material in the spinning solution is 10 mg / mL graphene oxide (the ratio of silk fibroin to conductive material is 50:1), and the draw ratio is 2.5. In step S3, the biodegradable material in the electrospinning solution is 10wt% polylactic acid-glycolic acid copolymer (PLGA), and the drug is 1mg / mL curcumin (the mass ratio of PLGA to drug is 100:1).

[0087] In step S4, the composite fiber and the edge of the electrospun film are inclined at a 30° angle, and then hot-pressed for 1 hour at 100°C and 1MPa.

[0088] The rest is the same as in Example 1, and will not be described again here.

[0089] Tests showed that the composite fiber prepared in Example 2 had a diameter of 40 μm and an electrical conductivity of 83 S / cm. Figure 11 These are the mechanical curves of the composite fiber prepared in Example 2 under wet and dry conditions, based on... Figure 11 It can be seen that the stress in the dry state is 31.3 MPa and the strain is 5.9%, while the stress in the wet state is 2.56 MPa and the strain is 38.7%, with the elastic modulus decreasing by 21.7 times. Immersing the composite fiber from Example 2 in PBS buffer resulted in a 46% mass loss after 3 months, indicating that it exhibits degradable properties over time.

[0090] Example 3 Example 3 is basically the same as Example 1, except that: In step S1, the conductive material in the spinning solution is a salt ion, specifically, 50 mg / mL sodium chloride is added to a 5 wt% silk fibroin nanofiber suspension (the ratio of silk fibroin to conductive material is 1:1); the coagulation bath is a saturated ammonium sulfate solution containing 3% ethanol by volume, and the draw ratio is 1.5. Testing showed that the composite fiber has a diameter of 64 μm and a conductivity of approximately 0.08 S / cm.

[0091] In step S3, the biodegradable material in the electrospinning solution is 7.5 wt% poly-L-lactic acid (PLLA), and the drug is 0.5 mg / mL minocycline (the mass ratio of PLLA to drug is 150:1).

[0092] In step S4, the composite fiber and the edge of the electrospun film are inclined at a 40° angle, and then hot-pressed for 12 hours at 60°C and 1MPa.

[0093] In step S5, the composite neural electrode is immersed in a 5 wt% regenerated silk fibroin solution, air-dried, and then soaked in an ethanol aqueous solution (ethanol volume percentage of 65%) for 20 minutes to temporarily harden the composite neural electrode.

[0094] The rest is the same as in Example 1, and will not be described again here.

[0095] The composite neural electrode prepared in Example 3 was placed in a release solution, which was a mixture of ethanol and PBS (5 mL of ethanol mixed with 45 mL of 10 mM PBS at pH 7.4). After 48 hours, the minocycline release rate reached 67%.

[0096] Example 4 Example 4 is basically the same as Example 1, except that: In step S1, the conductive material in the spinning solution is 10 mg / mL silver nanowires (the ratio of silk fibroin to conductive material is 5:1), the coagulation bath is a sodium chloride / polyethylene glycol solution (the mass ratio of sodium chloride is 5%), and the diameter of the conductive fiber obtained is 50 μm.

[0097] In step S3, the biodegradable material in the electrospinning solution is 10 wt% polycaprolactone (PCL), and the drug is 0.5 mg / mL vancomycin (the mass ratio of PCL to drug is 200:1).

[0098] In step S4, 20 composite fibers are fixed on an electrospinning film, with the composite fibers at a 10° angle to the edge of the electrospinning film and the spacing between adjacent composite fibers being 100 μm.

[0099] In step S5, the composite neural electrode is immersed in a 5 wt% regenerated silk fibroin solution, air-dried, and then treated with steam for 180 min to temporarily harden the composite neural electrode.

[0100] The rest is the same as in Example 1, and will not be described again here.

[0101] Figure 12 These are SEM images of electrospun films prepared using different biodegradable biomaterials in Examples 1-4; where PLLA corresponds to Example 3, PLA to Example 1, PLGA to Example 2, and PCL to Example 4. Figure 12 As shown, they all have obvious multi-level porous structures. Figure 13 This is a morphological diagram of the composite neural electrode of Example 4. It can be observed that the conductive fibers are integrated on a thin film composed of electrospun fibers. From the microscopic to the macroscopic, it is all fiber in shape, showing the characteristics of "all fiber".

[0102] Example 5 Example 5 is basically the same as Example 4, except that: In step S3, the biodegradable material in the electrospinning solution is PLGA, and the drug is 5 mg / mL tetracycline (PLGA to drug mass ratio is 20:1). Ultraviolet spectrophotometry analysis showed that the drug loading in the prepared porous fiber membrane was approximately 5 wt%.

[0103] In step S4, 20 composite fibers are fixed onto the electrospinning film, with the composite fibers at a 50° angle to the edge of the electrospinning film.

[0104] In step S5, the regenerated silk fibroin solution used for temporary hardening is treated with a methanol-water solution (volume ratio 1:1) for 30 min.

[0105] The rest are implemented in the same way as in Example 4, and will not be described again here.

[0106] Testing showed that the in vitro release period of tetracycline in the composite neural electrode obtained in Example 5 was approximately 6 weeks. The dry elastic modulus of the composite neural electrode prepared in Example 5 was approximately 55.2 MPa, and the wet elastic modulus was approximately 1.2 MPa.

[0107] Example 6 Example 6 is basically the same as Example 5, except that: In step S1, the spinning solution is prepared by adding MXene (Ti3C2T) to a 3 wt% silk fibroin nanofiber liquid crystal suspension. x The MXene content was 10 mg / mL (the ratio of silk fibroin to conductive material was 3:1); the coagulation bath was a saturated calcium chloride solution; and during the wet spinning process, the shear flow field induced the liquid crystal orientation of the nanofibers.

[0108] In step S4, 20 composite fibers are fixed on the surface of the electrospinning film, and the composite fibers are inclined at a 60° angle to the edge of the electrospinning film.

[0109] The rest is implemented in the same way as in Example 5, and will not be described again here.

[0110] According to the test, the dry elastic modulus of the composite neural electrode prepared in Example 6 is about 89.5 MPa, and the wet elastic modulus is about 4.7 MPa.

[0111] Example 7 Example 7 is basically the same as Example 6, except that: In step S1, MXene (Ti3C2T) is added to a 5.5 wt% silk fibroin nanofiber liquid crystal suspension. x The mixture was prepared by 3D printing, with MXene content of 10 mg / mL, to obtain a mixed solution (the ratio of silk fibroin to conductive material is 5.5:1). Using this mixed solution, conductive fibers of composite fibers were prepared by 3D printing extrusion molding. The inner diameter of the needle was 150 μm, the printing speed was 5 mm / s, the cross-section of the obtained conductive fiber was circular, and the conductivity of the obtained composite fiber was about 78 S / cm.

[0112] In step S4, the composite fiber and the edge of the electrospun film are at a 70° angle.

[0113] In step S5, the composite neural electrode is immersed in a 1 wt% regenerated silk fibroin solution, air-dried, and then steam-treated for 120 min to temporarily harden the composite neural electrode.

[0114] The rest is the same as in Example 6, and will not be described again here.

[0115] Figure 14 This is a photograph of the fiber orientation arrangement obtained by 3D printing using a 5.5 wt% silk fibroin nanofiber suspension, as shown in Example 7. This allows for the production of arrayed silk fibroin nanofibers. 3D printing technology enables personalized customization of fiber arrangement, facilitating mass production.

[0116] Example 8 Example 8 is basically the same as Example 5, except that: In step S1, conductive fibers are prepared using a dry spinning method, including: Silk fibroin was dissolved in a formic acid / calcium chloride solution (calcium chloride to formic acid ratio of 0.5g:10mL), and then genipin, polyethylene glycol diglycidyl ether, and 1,4-butanediol diglycidyl ether were added to obtain three spinning solutions containing different cross-linking agents. The silk fibroin content was 12wt%, the ratio of silk fibroin to conductive material (silver nanowires) was 2.4:1, and the ratios of cross-linking agent to silk fibroin were as follows: genipin to silk fibroin mass ratio was 1:20, polyethylene glycol diglycidyl ether to silk fibroin mass ratio was 1:2, and 1,4-butanediol diglycidyl ether to silk fibroin mass ratio was 2:5.

[0117] The above spinning solutions were extruded through needles and dried in hot air at 60°C. After the solvent evaporated, the fibers solidified to form conductive composite fibers.

[0118] In step S4, 20 composite fibers are fixed onto an electrospinning film, with the composite fibers at a 75° angle to the edge of the electrospinning film. Then, they are hot-pressed at 60°C and 1MPa for 6 hours. Next, the fibers are coiled around the direction of the composite fibers and heat-set at 100°C for 180 minutes to form a spiral-structured composite neural electrode.

[0119] The rest is implemented in the same way as in Example 5, and will not be described again here.

[0120] Comparing the composite fibers prepared from three spinning solutions containing different crosslinking agents in this embodiment, it was found that the strength of the composite fibers is significantly related to the crosslinking agent. Among them, the fiber prepared using polyethylene glycol diglycidyl ether has the highest strength, while the fiber crosslinked with 1,4-butanediol diglycidyl ether has the lowest strength.

[0121] Figure 15 This is an electron microscope image of the composite fiber obtained in Example 8 bonded to an electrospun film. The diameter of a single composite fiber obtained in this example is approximately 107 μm.

[0122] Example 9 This embodiment provides a composite neural electrode and its preparation method, specifically including the following steps: S1. Add MXene (Ti3C2T) to a 3 wt% silk fibroin nanofiber liquid crystal suspension. x Using MXene as the spinning solution (with a silk fibroin to conductive material ratio of 0.6:1), and a 5% sodium chloride-methanol solution as the coagulation bath, conductive composite fibers were produced by wet spinning. The conductivity was measured to be approximately 18 S / cm.

[0123] S2. The conductive fiber obtained in step S1 is coated with 5wt% polylactic acid to form an insulating encapsulation layer; then, the insulating encapsulation layer in a part of the conductive fiber is removed by etching with acetone to form exposed electrode points, and finally the composite fiber is obtained.

[0124] S3. Silk fibroin and polycaprolactone were blended at a mass ratio of 7:3 and dissolved in hexafluoroisopropanol to prepare a spinning solution with a total concentration of 10 wt% silk fibroin and polycaprolactone. Dexamethasone (30 mg / mL) and nerve growth factor (1 mg / mL) were added, with a polycaprolactone to drug mass ratio of 3.23:1. The electrospun fibers were collected using a high-speed rotating drum (1500 rpm) to obtain an electrospun film composed of oriented fibers with an orientation factor of 0.9.

[0125] S4. Take 50 composite fibers obtained in step S2 and arrange them parallel to each other on the surface of the porous fiber membrane obtained in step S3, with the composite fibers at an 80° angle to the edge of the porous fiber membrane and the spacing between adjacent composite fibers being 50 μm. Then, perform hot pressing fixation at 80℃ and 0.5MPa for 1 hour. Next, curl the composite fibers with the direction of the composite fibers as the curling axis and heat set at 60℃ for 30 minutes to form a spiral composite neural electrode.

[0126] S5. The composite nerve electrode obtained in step S4 is immersed in a 5 wt% silk fibroin solution, removed and air-dried, and then soaked in a methanol aqueous solution (45%, volume / volume) for 10 min to harden the composite nerve electrode.

[0127] Testing revealed that the dry elastic modulus of the composite neural electrode prepared in this embodiment is approximately 100 MPa, and the wet elastic modulus is approximately 5.7 MPa. The in vitro drug release period of the composite neural electrode in this embodiment is approximately one week.

[0128] According to cytotoxicity tests, after L929 cells were co-cultured with the extract of the composite neural electrode of this embodiment for 72 hours, the cell survival rate was over 90%.

[0129] In vitro degradation tests showed that after 8 weeks of degradation in PBS containing protease XIV, the composite neural electrode of this embodiment lost approximately 60% of its mass.

[0130] Figure 16 It is an electrospun fiber with an oriented structure obtained by high-speed rotation in Example 9. Figure 17This is a diffusion diagram of water droplets on the electrospun fibers with an oriented structure in Example 9. The direction of water droplet movement on the porous fiber film with a high orientation factor (collected at 1500 rpm) is consistent with the fiber alignment direction. When the speed of the high-speed rotating drum is reduced, the fiber orientation decreases. When the rotation speed is 50 rpm, the fibers are mainly disordered (orientation factor approximately <0.1). Therefore, the orientation factor of the fibers in the porous fiber film can be adjusted by controlling the drum rotation speed. At this time, the diffusion of water droplets on the film is random and has no significant directionality.

[0131] Example 10 Example 10 is basically the same as Example 8, except that: In step S1, a dry spinning process is used, and the concentration of silk fibroin in the spinning solution is 24 wt%, and the crosslinking agent is polyethylene glycol diglycidyl ether (with a mass ratio of 1:2 to silk fibroin).

[0132] In step S3, the electrospinning solution includes 10 wt% of the biodegradable material poly(L-lactate) (PLLA), 10 mg / mL of dopamine, and 20 mg / mL of glutamate (PLLA to drug mass ratio is 3.33:1).

[0133] In step S4, 20 composite fibers are fixed onto an electrospinning film, with the composite fibers at a 25° angle to the edge of the electrospinning film. Next, the fibers are coiled around the direction of the composite fibers as the coiling axis and heat-set at 80°C for 300 minutes to form a spiral-structured composite neural electrode.

[0134] The rest are implemented in the same way as in Example 8, and will not be described again here.

[0135] According to the test results, the dry elastic modulus of the composite neural electrode prepared in this embodiment is about 46.1 MPa, and the wet elastic modulus is about 7.4 MPa.

[0136] Figure 18 This is an optical microscope image of the cross-section of the composite neural electrode prepared in Example 10, showing the distribution of the composite fibers at the interface.

[0137] The composite neuroelectrode of this embodiment underwent in vitro drug release testing, and after one week, the drug release amount was 45.9% of the initial amount.

[0138] Example 11 The difference between Example 11 and Example 10 is that the electrospinning process conditions were adjusted in step S3 to verify the electrospinning effect under the conditions of a spinning voltage of 10kV or 25kV, a receiving distance of 10cm or 20cm, and a feed speed of 0.5mL / h, 1mL / h, and 3mL / h.

[0139] Figure 19 These are SEM images of the electrospun films obtained under different electrospinning conditions in Example 11 of this invention. Figure 19 It can be found that spinning parameters affect the diameter and surface morphology of the fiber. Under the process conditions of voltage of 10~25kV, receiving distance of 10~20cm, advance speed of 0.5~3mL / h, and receiving speed of 50~2000rpm, the electrospun film has a good multi-level pore structure, which can achieve good drug loading and controllable release.

[0140] Example 12 The only difference between Example 12 and Example 1 is that: In step S1, the conductive material is PEDOT:PSS, and the content of the conductive material accounts for 15 wt% of the silk fibroin nanofibers. Furthermore, after obtaining the conductive fiber, it is not dried to obtain a hydrogel-based composite conductive fiber.

[0141] In step S3, degummed silk is dissolved in a 9.3M lithium bromide aqueous solution (1g of degummed silk corresponds to 4mL of lithium bromide solution), placed in a 60℃ oven for 4 hours, and then removed. After dialysis and centrifugation, a silk fibroin solution is obtained. Then, after heating and concentration, nerve growth factor and brain-derived neurotrophic factor are added to obtain an electrospinning solution. In this electrospinning solution, the silk fibroin content is 20 wt%, the nerve growth factor content is 0.01mg / mL, and the brain-derived neurotrophic factor content is 0.01mg / mL (the mass ratio of silk fibroin to drugs is 20000:1). Electrospinning was performed using the electrospinning solution with the following parameters: voltage of 20 kV, receiving distance of 15 cm, feed speed of 0.5 mL / h, and roller receiving speed of 100 rpm. The electrospinned film was placed in a fume hood for drying. After drying, the film was immersed in a 90% volume concentration methanol solution for 30 min to induce a structural transformation of the silk fibroin fibers and ensure its stability in the wet state.

[0142] In S4, the angle between the edge of the film and the fiber direction is 10°. Then, the S1 composite fiber is bonded and fixed to the electrospun film with a 1wt% silk fibroin solution, followed by post-treatment with ethanol (90%) for 10 min to stabilize the composite structure, and then wound to obtain the composite nerve electrode.

[0143] After mechanical tensile testing, the modulus of the composite neuroelectrode in this embodiment was 121.3 kPa in a wet state. After implantation into the hippocampus of mice, recording electroencephalogram (EEG) signals revealed a high signal-to-noise ratio (>10 dB), and the ability to detect the firing signals of individual neurons.

[0144] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the electrospun film obtained by electrospinning in Example 1 is replaced with a polylactic acid (PLA) film obtained by solution casting. The preparation method includes: dissolving PLA in dichloromethane to prepare a PLA concentration of 10wt%, dropping it onto a glass slide for coating, and waiting for the solvent to evaporate to obtain a PLA film.

[0145] The rest is the same as in Example 1, and will not be described again here.

[0146] Testing revealed that the dry-state elastic modulus of the composite neural electrode in Comparative Example 1 was approximately 125.1 MPa, and the wet-state elastic modulus was approximately 123.7 MPa. The modulus variation was relatively small, and the overall modulus was significantly higher than that of the composite neural electrodes in Examples 1 and 11. This indicates that porous fiber films prepared by electrospinning have a significant advantage in reducing device modulus.

[0147] Figure 20 This is an electron microscope image of the PLA thin film in Comparative Example 1, based on... Figure 20 The PLA film of Comparative Example 1 has an uneven surface and a relatively dense structure, which is significantly different from the electrospun films in Examples 1-11.

[0148] According to the mercury porosimetry, the porosity of the electrospun film in Example 2 was 83.5%, while the porosity of the PLA film in Comparative Example 1 was 1.1%. It can be seen that the porosity of the electrospun film is significantly higher than that of the PLA dense film.

[0149] Figure 21 This is a comparison diagram of the water permeability of the electrospun film of Example 2 and the PLA film of Comparative Example 1. Deionized water was dropped onto the surfaces of the electrospun film of Example 2 and the PLA film of Comparative Example 1. The results showed that water rapidly spread and permeated into the network in the electrospun film; while water remained on the surface of the PLA film of Comparative Example 1. This indicates that using the electrospun film as a substrate for the composite neural electrode is beneficial for material transport.

[0150] In addition, the inventors of this case also conducted experiments with other raw materials, process operations, and process conditions described in this specification, referring to the aforementioned embodiments, and obtained relatively ideal results in all cases.

[0151] All aspects, embodiments, features, and examples of this invention should be considered illustrative and used to explain and illustrate the invention, but not to limit it. The scope of the invention is defined only by the claims.

[0152] Although the invention has been described with reference to the above embodiments, those skilled in the art will understand that various other changes, omissions, and / or additions can be made without departing from the spirit and scope of the invention, and that substantially equivalents can be substituted for elements in the described embodiments. Therefore, the invention is not intended to be limited to the specific embodiments disclosed, but rather to encompass all embodiments falling within the scope defined by the claims.

Claims

1. A composite neural electrode, characterized in that, It includes a porous fiber membrane and multiple composite fibers. The composite nerve electrode has a helical structure, which is formed by fixing multiple composite fibers to the surface of the porous fiber membrane and curling them up. The composite fiber includes conductive fibers and an insulating encapsulation layer. The insulating encapsulation layer is formed on a portion of the outer surface of the conductive fiber. The area at the first end of the conductive fiber not covered by the insulating encapsulation layer constitutes an electrode point. The porous fiber film has a multi-level pore structure, which includes micron-level inter-fiber pores and nano-level fiber surface pores. The porous fiber film is loaded with a drug. The first end of the composite nerve electrode is a contact area, which is composed of multiple electrode points; the second end of the composite fiber extends from the main structure of the composite nerve electrode and is used to connect to an external circuit; the middle region of the composite fiber is wrapped with a curled porous fiber membrane.

2. The composite neural electrode according to claim 1, characterized in that, The porous fiber film is an electrospun film; And / or, the porous fiber membrane comprises a first biodegradable material and a drug; And / or, the mass ratio of the first biodegradable material to the drug in the porous fiber membrane is 2.4:1 to 20000:

1.

3. The composite neural electrode according to claim 2, characterized in that, The first biodegradable material includes one or more combinations of polylactic acid-glycolic acid copolymer, L-polylactic acid, polycaprolactone, polylactic acid, or silk fibroin; And / or, the drug includes one or more of the following: anti-inflammatory drugs, neurotrophic factors, neurotransmitters, and antibacterial drugs.

4. The composite neural electrode according to claim 1, characterized in that, The conductive fiber comprises a second biodegradable material and a conductive material in a mass ratio of 0.6:1 to 50:1; And / or, the material of the insulating encapsulation layer includes one or more of polylactic acid-glycolic acid copolymer, polycaprolactone, and polylactic acid; And / or, the outer surface of the composite neural electrode also includes a temporary hardening layer made of regenerated silk fibroin.

5. The composite neural electrode according to claim 4, characterized in that, The second biodegradable material includes silk fibroin nanofibers and / or regenerated silk fibroin; And / or, the conductive material includes one or more combinations of MXene, carbon nanotubes, graphene, PEDOT:PSS, metal nanowires, or salt ions.

6. The composite neural electrode according to any one of claims 1-5, characterized in that, Multiple composite fibers are fixed to the surface of the porous fiber membrane in a parallel arrangement; And / or, when the composite fiber is fixed to the surface of the porous fiber membrane, the composite fiber forms an angle of 10 to 80° with at least one edge of the porous fiber membrane; And / or, the dry elastic modulus of the composite neural electrode is 1 MPa to 100 MPa, and the wet elastic modulus is 100 kPa to 10 MPa.

7. A method for preparing a composite neural electrode, characterized in that, include: A first spinning solution comprising a first biodegradable material and a drug is provided, and the first spinning solution is used to form a porous fiber membrane loaded with the drug using an electrospinning process. A second spinning solution containing a second biodegradable material and a conductive material is provided. The second spinning solution is used to form conductive fibers, and an insulating encapsulation layer is covered on a portion of the surface area of ​​the conductive fibers. The insulating encapsulation layer does not cover the first end of the conductive fibers to form exposed electrode points, thereby obtaining composite fibers. Multiple composite fibers are fixed to the surface of the porous fiber membrane, then rolled up, and after shaping, a spiral composite nerve electrode is obtained. The first end of the composite nerve electrode is a contact area, which is composed of electrode points on multiple composite fibers; the second end of the composite fiber extends from the main structure of the composite nerve electrode and is used to connect to an external circuit; the middle region of the composite fiber is wrapped by a curled porous fiber membrane.

8. The preparation method according to claim 7, characterized in that, The first biodegradable material in the first spinning solution has a content of 5~20wt%, and the drug content has a content of 0.01mg / mL~31mg / mL.

9. The preparation method according to claim 7, characterized in that, The second biodegradable material in the second spinning solution is 3-24 wt%, and the conductive material is 2 mg / mL to 50 mg / mL. And / or, the method of forming the second spinning solution into conductive fibers includes any one of wet spinning, dry spinning, and 3D printing.

10. The preparation method according to claim 7, characterized in that, Also includes: After the shaping process, the obtained composite neural electrode is subjected to a temporary hardening treatment, which includes: immersing it in a regenerated silk fibroin solution, removing it and drying it, and then performing physical or chemical treatment to form a temporary hardened layer on the outer surface of the composite neural electrode.

11. The preparation method according to claim 10, characterized in that, The physical treatment includes either steam treatment or heating; and / or, the chemical treatment includes impregnation with an aqueous solution containing methanol and / or ethanol.

12. The preparation method according to claim 7, characterized in that, Multiple composite fibers are fixed to the surface of a porous fiber membrane in a parallel arrangement. And / or, when fixing the composite fiber to the surface of the porous fiber membrane, the composite fiber is inclined at an angle of 10 to 80° to at least one edge of the porous fiber membrane.

13. The preparation method according to claim 7, characterized in that, The first biodegradable material includes one or more combinations of polylactic acid-glycolic acid copolymer, L-polylactic acid, polycaprolactone, polylactic acid, or silk fibroin; And / or, the second biodegradable material includes silk fibroin nanofibers and / or regenerated silk fibroin; And / or, the conductive material includes one or more combinations of MXene, carbon nanotubes, graphene, PEDOT:PSS, metal nanowires or salt ions; And / or, the material of the insulating encapsulation layer includes one or more of polylactic acid-glycolic acid copolymer, polycaprolactone, and polylactic acid.

14. A composite neural electrode, characterized in that, It is prepared by the preparation method according to any one of claims 7-13.

15. A brain-computer interface device, characterized in that, Includes the composite neural electrode as described in any one of claims 1-6 and 14.

Citation Information

Patent Citations

  • Flexible electrodes and methods of making the same

    CN113710309A

  • Fiber nerve electrode and preparation method thereof

    CN115538163A

  • A breathable, high substrate adhesion, flexible and stretchable neural electrode and its preparation method and application

    CN115998299B